PERENCANAAN TATA LETAK GUDANG PENGGUNAKAN METODE SHARED STORAGE DI PABRIK PLASTIK KOTA SEMARANG - Firman Ardiansyah Ekoanindiyo; Yaumal Agit Wedana (Jurnal Ilmiah Dinamika Teknik, 2012)
Storage in the manufacturing industry is an important role, it may not yield immediate distribution to all its customers. This leads to the need for warehouse and storage system is good. Warehouse is either not large in size should be supported because if good storage system and a good inventory warehouse use will be maximized. The problems faced by the plastics factory occurred in the warehouse of raw materials and finished products. Less favorable arrangement of goods in the warehouse procedures cause problems in the warehouse, so the barn seem cramped and poorly organized. Conditions warehouse layout that is not based on a comprehensive layout design can lead to inefficiencies in time retrieval and storage of materials and material handling operators difficult due to limited warehouse. The process of product placement on shared storage method is to construct storage areas based on the extensive Lantau warehouse, and then sorted the area closest to the area farthest from the doorway I/O, so the placement of the items will be sent immediately placed on the most close and so on. Shared storage is a method of setting the layout of the warehouse using the principle of FIFO (First In First Out) where the goods were quickly dispatched placed in the storage area closest to the entrance-exit (I/O). Methods would be better spent on the kind of plant which has the same size or product dimensions are not much different. Because each storage area may be occupied by different products vary based on production time and date of delivery of the product. Keywords: Storage, Warehouse Layout, Method of Shared Storage